2007
DOI: 10.1007/s10660-007-9000-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Internet general privacy concern on customer behavior

Abstract: Privacy and its related variables are important determinants of customer behavior in the electronic market. This paper aims to examine the concern for customer privacy on the Internet, mainly with regard to disclosing personal information online. Furthermore, by establishing an experimental situation, we will analyze how this behavior is influenced by familiarity with the website sponsor, the level of control over the information the customer has and the sensitivity of the information requested.The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 64 publications
(149 reference statements)
2
65
0
4
Order By: Relevance
“…Putting this new scale into practice, we found that users with a higher level of concern for online privacy and higher privacy self-efficacy chose privacy protection behavior over usability and reported lower privacy paradox behavior. These results were in accordance with some of the above studies (Akhter 2014;Awad & Krishnan 2006;Castañeda & Montoro 2007;Heirman, Walrave & Ponnet 2013;Hoffman et al 1999;Lee & Letho 2010;Phelps, Nowak & Ferrell 2000;Phelps, D'Souza & Nowak 2001;Potoglou, Palacios & Feijóo 2015;Taylor, Davis & Jillapalli 2009). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Putting this new scale into practice, we found that users with a higher level of concern for online privacy and higher privacy self-efficacy chose privacy protection behavior over usability and reported lower privacy paradox behavior. These results were in accordance with some of the above studies (Akhter 2014;Awad & Krishnan 2006;Castañeda & Montoro 2007;Heirman, Walrave & Ponnet 2013;Hoffman et al 1999;Lee & Letho 2010;Phelps, Nowak & Ferrell 2000;Phelps, D'Souza & Nowak 2001;Potoglou, Palacios & Feijóo 2015;Taylor, Davis & Jillapalli 2009). …”
Section: Discussionsupporting
confidence: 92%
“…The following types of factors have been examined in the literature: 1. Socio-demographic factors such as gender and age (Baddeley 2011;Castañeda & Montoro, 2007;Milne & Boza 1999;Phelps et al 2000). Numerous studies found that women publish more personal information than men (Acquisti & Gross 2006;Feng & Xie 2014;Fogel & Nehmad 2009;Hoy & Milne 2010;Kolek & Saunders 2008;Tufekci 2008), and rarely adopt privacy protection behavior (Milne, Rohm & Bahl 2004;Sheehan 1999;Yao & Linz 2008).…”
Section: Factors Of Online Self-disclosurementioning
confidence: 99%
“…People are most likely to falsify sensitive personal data, but not those deemed relevant for the completion of a specific online transaction (Metzger, 2007). The type of information that is requested is also an important indicator of whether or not people will decide to disclose their information -the more sensitive they are to the requested information, the weaker are their intentions to disclose them online (Castaneda & Montoro, 2007).…”
Section: Information Withholding and Incompletementioning
confidence: 99%
“…If the data requested by online organizations are assessed to be very sensitive, Internet users' perceptions of the risks involved in sharing personal information online would expectedly increase (Malhotra, Kim, & Agarwal, 2004), which could reduce their inclination to disclose them whenever requested (Castaneda & Montoro, 2007). Several studies have shown that Internet users are reluctant to disclose personally-identifiable information, such as their complete names or contact addresses (Acquisti & Grossklags, 2005;Metzger, 2006;Phelps, Nowak, & Ferrell, 2000), and financial information, such as income and credit card numbers (Metzger, 2006;Phelps, D'Souza, & Nowak, 2001;Phelps, Nowak, & Ferrell, 2000).…”
Section: Assessment Of Data Sensitivity and Risk Perceptionsmentioning
confidence: 99%
“…Vice versa Internet customers do not perceive the advertising as a contract, but as an intrusive and annoying deviation (Mathews, 2000;Gaffney, 2001). Nowadays, there are some studies suggesting that the most loyal users of the Internet perceive online advertisements as a negative factor as it imply the constant needs of protecting their privacies (Castaneda & Montoro, 2007). The use of information collection, in fact, cannot be controlled and, frequently, users do not know that web sites are collecting their private data (Milne, 2000).…”
Section: Strengths and Weaknesses Of Advertising In Snssmentioning
confidence: 99%